A Case Series of Bee Sting Keratopathy With Different Outcomes in Malaysia - Ang, Wen-Jeat (Cureus, 2017)
We report three patients with corneal bee sting at our tertiary care center in a three-year period starting from 2014 to 2016. All patients sustained a bee sting injury to the cornea. All patients received early preoperative topical antibiotics, topical cycloplegic and intensive topical steroids. However, the timing of the initial presentation, the duration, and the location of the retained stinger differed in each case leading to different postsurgical outcomes.